Transformational Leadership on Employee Performance at PT. Sarana Sinar Sulawesi - Nuraini Nuraini; Arnas Hasanuddin (International Journal of Management Research and Economics, 2025)
The purpose of this study is to ascertain the impact of work motivation (X2), performance (Y), and transformational leadership (X1) on the quality of corporate performance. This study uses quantitative methods. Information sources from primary and secondary data were obtained using a straightforward probability sampling technique. Multiple linear regression, hypothesis testing, coefficient of determination, and classical assumption tests were employed in the data analysis. The software SPSS Version 22 was used for this. Information was gathered by means of surveys given to fifty-two individuals at PT. Sarana Sinar Sulawesi, situated in Tamalanrea, Makassar City. The study's findings indicate that the transformational leadership variable significantly affects worker performance, with t = 8.375 and a p-value of 0.000 < 0.05.